2006
DOI: 10.2113/12.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Clustering of Major Solutes: Use as a Tracer for Evaluating Interbasin Groundwater Flow into Indian Wells Valley, California

Abstract: Many previous studies have demonstrated use of specific solutes or isotopes as tracers of groundwater flow. We present a technique that uses standard hydrochemical information to create statistically based hydrochemical facies, which are then used as tracers of groundwater flow. This approach reduces potential subjective bias during interpretation of single tracer data in complex systems with multiple sources or conflicting multiple tracer data. Standard hydrochemical data from 1,368 water samples that spanned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Another possibility is that some of the water originated in higher elevation basins. Güler & Thyne (2006) found evidence for interbasin flow in the southern Sierra Nevada, and Sylvester (2007) has suggested that groundwater from Independence Lake might feed springs on the western side of the basin. While there is no direct evidence for this, the possibility of interbasin flow is a concern in any area where the hydrogeology has not been studied in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that some of the water originated in higher elevation basins. Güler & Thyne (2006) found evidence for interbasin flow in the southern Sierra Nevada, and Sylvester (2007) has suggested that groundwater from Independence Lake might feed springs on the western side of the basin. While there is no direct evidence for this, the possibility of interbasin flow is a concern in any area where the hydrogeology has not been studied in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Catchments may also be leaky at river‐basin scales. Güler and Thyne (2006) used geochemical tracers to show that water originating in the Kern could be found in a different river basin on the eastern side of the Sierra Nevada. As a fraction of the overall water balance, this amount is likely to be smaller for river basins than for catchments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the subsurface structure of the critical zone has been identified as the biggest knowledge gap in the effort to incorporate hillslope-scale hydrological processes into Earth System Models (Fan et al, 2019) Catchments may also be leaky at river-basin scales. Güler and Thyne (2006) used geochemical tracers to show that water originating in the Kern could be found in a different river basin on the eastern side of the Sierra Nevada. As a fraction of the overall water balance, this amount is likely to be smaller for river basins than for catchments.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, they "bookended" the intercatchment groundwater transfer, showing its termination at the second catchment in a three-catchment catena (Figure 11). Güler and Thyne (2006) traced the origin of the shallow groundwater in the Indian Wells Valley (IWV), below the eastern flank of Sierra Nevada Range in southern California, to source regions outside of the topographic basin. Geochemical clustering analysis pinpointed chemical facies diagnostic of water sources, tracing groundwater flow via dense fractures from the Sierra Nevada mountains west of the topographic divide.…”
Section: Linking Importing To Exportingmentioning
confidence: 99%